1989
DOI: 10.1038/342955a0
|View full text |Cite
|
Sign up to set email alerts
|

Style self-incompatibility gene products of Nicotlana alata are ribonucleases

Abstract: Self-incompatibility in flowering plants is often controlled by a single nuclear gene (the S-gene) having several alleles. This gene prevents fertilization by self-pollen or by pollen bearing either of the two S-alleles expressed in the style. Sequence analysis shows that three alleles of the S gene of Nicotiana alata encode style glycoproteins with regions of defined homology. Two of the homologous regions also show precise homology with ribonucleases T2 (ref. 4) and Rh (ref. 5). We report here that glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
441
3
12

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(461 citation statements)
references
References 12 publications
5
441
3
12
Order By: Relevance
“…S-RNase is a basic glycoprotein with RNase activity (McClure et al, 1989). RNase activity of S-RNase is required for the pistil to reject self-pollen Royo et al, 1994;McCubbin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…S-RNase is a basic glycoprotein with RNase activity (McClure et al, 1989). RNase activity of S-RNase is required for the pistil to reject self-pollen Royo et al, 1994;McCubbin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Box 50, Auckland, New Zealand. S RNases (McClure et al, 1989). These glycoproteins are very abundant in the extracellular matrix of the transmitting tract and are also expressed in the stigma and in the epidermis of the placenta (Cornish et Anderson et al, 1989;McClure et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…S allele-specific pollen rejection occurs as pollen tubes grow through the extracellular matrix of the stylar transmitting tract (Newbigin et al, 1993). The products of the S locus in the style are the To whom correspondence should be addressed.S RNases (McClure et al, 1989). These glycoproteins are very abundant in the extracellular matrix of the transmitting tract and are also expressed in the stigma and in the epidermis of the placenta (Cornish et Anderson et al, 1989;McClure et al, 1993).…”
mentioning
confidence: 99%
“…21, Japan, 10%), local homology around the essential residues is fairly high. It was predicted that the glyeoprotein must have the RNase specific activity [8], and in fact McClure et al [9] reported that glycoproteins isolated from style extracts of Nicotiana ctlata exhibited ribonuclease activities. Therefore, it seems that this new class of RNase involving RNase Rh.…”
Section: Introductionmentioning
confidence: 99%